Continuous Synthesis of a Green Fuel Additive Mixture with Highest Quantities of Solketalacetin and Solketal and Lowest Amount of Diacetin from Biodiesel-Derived Glycerol - Gorji,Yadollah M. (2018)
This work presents a continuous, easy-to-scale-up system for glycerol conversion to a valuable fuel additive mixture such as solketalacetin ((2,2-dimethyl-1,3-dioxolan-4-yl)methyl acetate), solketal and minimum amount of diacetin with no byproducts. A two-stage reaction was conducted to synthesize the mixture. At first, glycerol was reacted with acetic acid in a continuous system to synthesize monoacetin using a small plug flow reactor and central composite design to optimize the variables related to monoacetin synthesis. Finally, an acetic acid:glycerol mole ratio of 3.7:1, a temperature of 79 °C, a flow rate of 0.9 mL min-1, and a pressure of 1 bar were determined as the optimum conditions. At the optimum condition, predicted and experimental yields of monoacetin were 63 and 62%, respectively. In the next stage, monoacetin and the residual glycerol were reacted with acetone to obtain a mixture of solketalacetin, solketal, and diacetin with the mole percentage of 62, 30, and 8%, respectively.